(untitled) - Tillery, Bill W. (Dubuque, IA, 1995)
Extensively used in the first edition, this conceptual physics laboratory manual is back, and it's better than ever. Tillery's Laboratory Manual in Conceptual Physics provides your non-science students with a hands-on introduction to experimental methods of scientific investigation.
Keywords: Physical sciences,Physics; Laboratory manuals,Laboratory manuals